Penerapan Model Public Service Integrated dalam Mal Pelayanan Publik Huma Betang Kota Palangka Raya - Al Hilal, Ahmad Lisyam (Public Sphere Review, 2024)
The Public Service Mall is the government's effort to improve the quality of the bureaucratic system, with the aim of providing satisfaction to the community through providing services in one location. This Public Service Mall aims to help the community and provide convenience in managing business administration. The aim of this research is to explain the implementation of the Palangkaraya City Public Service Mall, namely Huma Betang. The research method used in this research is descriptive qualitative. Data collection techniques use interviews, observation and documentation. The results of this research show that the Huma Betang Public Service Mall, Palangka Raya City is included in the yellow zone category at 71.64%. The Ombudsman of the Republic of Indonesia assessed a series of structured steps starting with the preparation of a Memorandum of Understanding and Cooperation Agreement. Next there is the formation and design of service tenants, information systems, management and registration, monitoring and evaluation. In the context of managing complaints and input, as well as coordination and regular meetings between agencies or tenants, this mechanism becomes a solid foundation for the delivery of integrated services. The service mechanism process not only includes the operational stage but also includes information related to service costs. Internal aspects such as allocation of operational funds and management of human resources. External factors such as the construction of the MPP main building and collaboration with related agencies are expected to provide solutions to the problems faced.